Optimization of starch isolation from taro using combination of enzymes and comparison of properties of starches isolated by enzymatic and conventional methods - Sit, Nandan (J Food Sci Technol, 2014)
The optimization of enzymatic starch isolation process from taro tubers using cellulase and xylanase was carried out. The functional properties of starch isolated by optimized enzymatic process were compared with starch isolated by conventional method without the use of enzymes. A central composite rotatable design (CCRD) with four numerical factors was employed to design the experiments. The numerical factors were cellulase concentration (0–100 U/100 g tuber), xylanase concentration (0–100 U/100 g tuber), temperature of incubation (30–50 °C) and incubation time (1–5 h). Statistical analysis showed that the main effects of all the factors were significant on starch yield and effect of cellulase was more significant compared to xylanase. The effectiveness of xylanase in increasing the yield of starch from taro tubers confirmed that xylan is an important component of the cell walls of taro tubers. The optimized condition with maximum starch yield (17.22 %) was obtained when cellulase and xylanase concentration were 299.86 and 300 U/100 g tuber, temperature was 35 °C and incubation time was 2 h. The swelling of the starch granules increased whereas solubility decreased for enzymatic method. The clarity of the starch paste isolated by enzymatic method was found to be better compared to the clarity of starch paste isolated by conventional method. The pasting temperature of the starch paste was slightly higher and viscosity was lower for the starch isolated by enzymatic method. Freeze-thaw stability of the starch paste was also found to be better for the enzymatically isolated starch.